Pengaruh Kepemimpinan Transformasional dan Kepuasan Kerja terhadap Kinerja ASN di BKPSDM Bekasi - Intan Indra Putri; Mahmud Syarif; Desy Tri Anggarini (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
This study aims to analyze the influence of job satisfaction and transformational leadership on the performance of State Civil Apparatus (ASN) employees at the Bekasi City Personnel and Human Resources Development Agency (BKPSDM). The background of this study is based on the importance of leadership and job satisfaction as key factors in improving employee performance to support optimal public services. The study used a quantitative approach with data collection through distributing questionnaires to 53 respondents. The analysis technique used was multiple linear regression to measure the extent of the influence of the independent variables (transformational leadership and job satisfaction) on the dependent variable (employee performance). The results of the analysis showed that both independent variables had a positive and significant influence on ASN performance. Transformational leadership had a coefficient of 0.415 with a significance value of 0.001, while job satisfaction showed a coefficient value of 0.372 and a significance value of 0.001. The coefficient of determination (R²) value of 0.652 indicates that 65.2% of the variation in employee performance can be explained by transformational leadership and job satisfaction. The remaining 34.8% is explained by other variables outside the model. Based on the results of the hypothesis testing, all alternative hypotheses (Ha1, Ha2, and Ha3) were accepted. This means that, both partially and simultaneously, transformational leadership and job satisfaction significantly influence employee performance. This finding reinforces the importance of an inspirational leadership style, capable of providing motivation, vision, and individual attention to subordinates, as well as the importance of creating a supportive and satisfying work environment for employees. These two aspects have proven to be effective strategies for improving ASN performance, particularly within the Bekasi City BKPSDM environment.